Health Nutrition Education and Strengthening Indonesian Culture Among Indonesian Migrant Workers Children in Malaysia - Rahmaddiansyah, Refa; Azizah, Aghasi Yanda Wafa; Abdurrahman, Adisa Muhammad; Muftiana, Sintya Nur; Haq, Addienul; Riswanti, Laila Wulan; Jalilah, Thurfah Hashifah; Masthurina, Ulfa; Hrp, Maritza Briliani Namora; Tambunan, Mega Intan; Pelani, Achmad Aziz; Noviar, Tita Falisha; Abdurrahman, Thariq; Azizah, Siti Nur (Jurnal Pengabdian Masyarakat Isei, 2024)
In September 2015, the United Nations General Assembly adopted the 2030 Agenda for Sustainable Development, featuring 17 Sustainable Development Goals (SDGs) that address global issues like poverty, inequality, and education. This agenda highlights the importance of inclusivity, particularly regarding the vulnerabilities of migrant populations. Indonesian migrant children in Malaysia face significant barriers to education and health due to socio-economic factors and cultural challenges, often lacking access to formal education and relying on alternative learning centers like Sanggar Bimbingan. To tackle these issues, the "Anak CERIA" program was initiated by the international volunteer team from October 1 to 4, 2024, at Sanggar Bimbingan Sekolah Indonesia Kuala Lumpur (SIKL). A team of 13 diverse volunteers conducted integrated learning activities focused on health education and cultural awareness, using materials from the "Isi Piringku" nutritional guide. The program aimed to enhance the children's understanding of balanced nutrition and promote their cultural identity through interactive sessions about local foods and iconic Indonesian landmarks. A total of 41 children participated, benefiting from a collaborative learning approach that included puzzles and flashcards. Nutritional assessments were conducted to evaluate dietary habits, and traditional dances were taught to foster cultural pride. The program effectively supported the children's education and health while emphasizing the need for ongoing research into parental involvement. Overall, "Anak CERIA" aligns with the SDGs for 2030 and aims to inspire similar initiatives in the future.